Pemilihan Profesi Akuntan: Pengaruh Persepsi Penghargaan Finansial, Pelatihan Profesional, Nilai-Nilai Sosial Dan Lingkungan Kerja (Studi Pada Mahasiswa Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Tangerang) - abbas, Dirvi surya; Eksandy, Arry; Hakim, Mohamad Zulman (Universitas Muhammadiyah Tangerang, 2020)
This study aims to obtain evidence regarding the influence of Perception of Financial Awards, Professional Training, Social Values and Work Environment on the Selection of the Accounting Profession. This study uses purposive sampling and accidental sampling techniques and obtained a sample of 101 accounting students in 2016 taken in the academic year 2018/2019. Hypothesis testing in this study was conducted using multiple linear regression analysis.The results of the first research hypothesis indicate that in the model there is a significant positive effect of the Perception of Financial Awards on the Accountant's Professional Selection, with the results of tcount 3,517> ttable 1,985 and sig. 0.001 <0.05, then the results of the second research hypothesis indicate that in the model there is a significant positive effect of Professional training on the Accountants Professional Selection, with tcount 3,772> ttable 1,985 and sig. 0,000 <0.05, then the results of the third research hypothesis show that in the model there is no significant effect of social values on the Professional Selection of Accountants, with tcount -1.254 < ttable 1,985 and sig. 0.213> 0.05, and then the results of the fourth research hypothesis indicate that in the model there is a significant positive effect of the Work Environment on the Professional Selection of Accountants, with tcount 2.212> ttable 1.985 and sig. 0.029 <0.05.